2005
DOI: 10.1211/0022357055876
|View full text |Cite
|
Sign up to set email alerts
|

Educating Australian pharmacists about the use of online information in community pharmacy practice

Abstract: Objectives Community pharmacists practice in an information technology‐rich society, however many have not been educated in internet use for professional practice. The aims of this study were to investigate how community pharmacists use the internet in their practice; to develop an intervention to address their educational needs; and to examine the benefits and weakness of a flexible delivery programme. Method We conducted two focus groups investigating community pharmacists' internet use and education needs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Another surveyed allied health professionals (AHPs), including pharmacists, in Australia about their use of electronic evidence resources 53. A further Australian study, based on community pharmacists, combined pre-intervention focus groups with a post-educational intervention evaluative survey 51. The final study used mixed methods to review informatics content, including computer and digital literacy skills, in pharmacy education by mapping syllabi returned by schools of pharmacy against the US ACPE Standards 52…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another surveyed allied health professionals (AHPs), including pharmacists, in Australia about their use of electronic evidence resources 53. A further Australian study, based on community pharmacists, combined pre-intervention focus groups with a post-educational intervention evaluative survey 51. The final study used mixed methods to review informatics content, including computer and digital literacy skills, in pharmacy education by mapping syllabi returned by schools of pharmacy against the US ACPE Standards 52…”
Section: Resultsmentioning
confidence: 99%
“…Based on a literature review, Bearman et al51 found ‘there was little or no information regarding community pharmacists’ skills and knowledge levels or how they currently employ internet technologies’. Through focus groups, they identified a ‘wide variety of technical knowledge and skills.’ Where access was available, participants most commonly used the internet at work for email and to search pharmacy-related topics, such as medicines or patient information, with a small proportion contributing to a pharmacy message forum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Australian studies have highlighted the need for pharmacists to have skills in identifying and critiquing literature that consumers use for advice (Williams & Wong, 2003;Bearman et al, 2005). This is supported by the Pharmaceutical Society of Australia Professional Practice Standards that highlight the importance of pharmacists using evidence-based resources and their ability to critically interpret information to provide to consumers (Pharmaceutical Society of Australia, 2006).…”
Section: Unit Aim 4: Be Able To Critique Pharmacy Research Papersmentioning
confidence: 99%
“…Many pharmacists have not been educated to use the internet for professional practice (Bearman, Bessell, Gogler, & McPhee, 2005) and may view this information as unreliable (Williams & Wong, 2003). More than ever then, pharmacists must be able to critically appraise research reports and assess the claims of pharmaceutical companies, whether the information comes from the internet or from more traditional sources such as peer-reviewed journal articles or books.…”
Section: Introductionmentioning
confidence: 99%